Information computing and applications international conference, ICICA 2010, Tangshan, China, October 15-18, 2010, proceedings. Part I - ICICA 2010 (2010 Tangshan, China); Zhu, Rongbo; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the proceedings of the International Conference on Information Computing and Applications, held in Tangshan, China, in October 2010.
Electronic reproduction.
Keywords: Computer science -- Congresses; Information technology -- Congresses; Electronic books